Vascular cognitive impairment in patients after acute myocardial infarction - M. M. Petrova; A. R. Leiman; S. A. Ustyugov; N. A. Schneider; A. V. Petrov (Российский кардиологический журнал)
Patients with acute myocardial infarction (MI) are identified by Russian and foreign experts as a risk group for moderate vascular cognitive impairment (VCI) and vascular dementia. As a result of various pathogenetic mechanisms, patients with MI develop the so-called cardiac cerebral syndrome, which makes a significant contribution to global cognitive impairment in this group of patients. The impact of MI on the risk and progression of cognitive impairment is one of the key links in improving the prognosis and quality of life in patients after MI. The aim of the review was to analyze the incidence of moderate VCI and vascular dementia in patients with MI in the acute and late periods.